2023
DOI: 10.1108/mmms-12-2022-0283
|View full text |Cite
|
Sign up to set email alerts
|

Transient analysis of variable thickness multi-directional functionally graded plates using isogeometric analysis

Abstract: PurposeThe main objective of this study is to develop a numerical model based on Isogeometric Analysis to study the dynamic behavior of multi-directional functionally graded plates with variable thickness.Design/methodology/approachA numerical study was conducted on the dynamic behavior of multi-directional functionally graded plates. Rectangular and circular plates with variable thickness are taken into investigation. The third-order shear deformation plate theory of Reddy is used to describe the displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…where  stands for the plate's reference plane and   qt , which is the distributed load applied to the plate's upper surface, is dependent on the time t variable. For detailed information regarding the quantities specified in the preceding equation, we refer readers to [26].…”
Section:  mentioning
confidence: 99%
See 2 more Smart Citations
“…where  stands for the plate's reference plane and   qt , which is the distributed load applied to the plate's upper surface, is dependent on the time t variable. For detailed information regarding the quantities specified in the preceding equation, we refer readers to [26].…”
Section:  mentioning
confidence: 99%
“…where   qt denotes the load vector and M and K stand for the mass and stiffness matrices, respectively. The readers may find further details in [26]. In this analysis, only structural damping of the plate is considered.…”
Section: Isogeometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…where Ω represents the reference plane of the plate; q (t) is the distributed load exerted on the upper surface of the plate and is dependent on the variable of time t. Readers can consult Ref. [5] for specific information about the quantities mentioned in the equation above.…”
Section: Plate Formulationmentioning
confidence: 99%
“…Ootao et al [4] investigated the transient thermoelastic problem of a functionally graded plate with piecewise exponential law caused by a nonuniform heat supply. Tran and Thai [5] used isogeometric analysis to investigate transient analysis of multi-directional functionally graded plates. And several other studies as shown in [6,7].…”
Section: Introductionmentioning
confidence: 99%